GELARAN FASHION SHOW “KAWULA MUDA FESTIVAL (TEMA GELORA WASTRA)” SEBAGAI WUJUD APRESIASI BERKARYA - Aninda Dyah Hayu Pinasti Putri (Akademi Seni dan Desain Indonesia Surakarta, 2025)
This community service initiative aimed to provide a platform for appreciation and creative expression for young designers, fashion vocational high school students, and fine arts academy students through a fashion show titled